2019
DOI: 10.1002/aqc.3080
|View full text |Cite
|
Sign up to set email alerts
|

Fishing for conservation of freshwater tropical fishes in the Anthropocene

Abstract: The ecosystem services provided by freshwater biodiversity are threatened by development and environmental and climate change in the Anthropocene. Here, case studies are described to show that a focus on the shared dependence on freshwater ecosystem functioning can mutually benefit fisheries and conservation agendas in the Anthropocene. Meeting the threat to fish biodiversity and fisher livelihood is pertinent in developing regions where there is often a convergence between high biodiversity, high dependency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 87 publications
1
13
0
1
Order By: Relevance
“…Given that fishing requires healthy river ecosystems, fishers share a common agenda with biodiversity conservation. This common agenda enables well-informed fishers to act as partners with conservationists in their demand for river conservation (Phang et al, 2019). It is apparent that the first generation of recreational fishers in the region have been formed by former riverside dwellers who no longer depend on fishing to supply their nutritional needs, livelihoods or income (da Silva and Silva, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that fishing requires healthy river ecosystems, fishers share a common agenda with biodiversity conservation. This common agenda enables well-informed fishers to act as partners with conservationists in their demand for river conservation (Phang et al, 2019). It is apparent that the first generation of recreational fishers in the region have been formed by former riverside dwellers who no longer depend on fishing to supply their nutritional needs, livelihoods or income (da Silva and Silva, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…navigation, irrigation, hydropower and commercial fisheries), others are hard to estimate accurately. In particular, the importance of recreational fisheries is underestimated in many regions, resulting in fishers being placed as inferior stakeholders when the multiple uses of inland waters are considered (Phang et al, 2019). Additionally, due to human population growth, fish stocks of both marine and inland waters have been under increasing fishing pressure (Funge‐Smith, 2018; Brownscombe et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Linking the management of freshwater resources with aquatic conservation is also explored by Phang et al (), by uniting the shared objectives of sustainable inland fisheries and freshwater biodiversity conservation. This innovative work demonstrates the misconception that fishing is an inherently adverse activity for freshwater biodiversity.…”
Section: Invigorating Freshwater Conservation Approachesmentioning
confidence: 99%
“…Rather, the quest for the twin goals of sustainable fisheries and aquatic biodiversity conservation can be advanced by empowering fishing concerns, be they commercial or artisanal. The work presented by both Abell et al () and Phang et al () describes two approaches that unite resource provisioning and conservation goals, leading to greater socio‐economic and political capacity to effect beneficial change. These align to similar approaches, such as that proposed by Noble, Fulton, and Pittock (), who demonstrated that focusing on the conservation of a keystone freshwater species (Murray crayfish, Euastacus armatus ) can also support the achievement of a number of socio‐economic goals in south‐east Australia.…”
Section: Invigorating Freshwater Conservation Approachesmentioning
confidence: 99%
“…Upaya yang dapat dilakukan dalam pelestarian ikan bilih antara lain pengaturan penangkapan baik ukuran ikan maupun waktu penangkapan; penetapan daerah suaka serta penebaran kembali ikan bilih (Koeshendrajana, Purnomo & Kartamihardja, 2005;Gunarto, 2009;Kartamihardja, 2009;Syandri, Junaidi & Azrita, 2011). Pengaturan penangkapan merupakan upaya pengelolaan sumber daya ikan yang bertangguang jawab dan berkelanjutan (Phang et al, 2019) dan penetapan suaka adalah upaya yang dilakukan dalam konservasi sumber daya ikan air tawar di India (Sarkar, Pathak, & Lakra, 2008). Namun saat ini belum ada peraturan yang disepakati mengenai pengelolaan ikan bilih (Syandri et al, 2014).…”
unclassified